A High-Voltage, Multi-Metal LiNi0.35Cu0.1Mn1.45Fe0.1O4 Spinel Cathode for Lithium Batteries. Issue 3 (22nd March 2021) - Wei, Shuangying; Di Lecce, Daniele; Hassoun, Jusef
Abstract : A LiNi0.35 Cu0.1 Mn1.45 Fe0.1 O4 spinel cathode exploiting the multi-metal approach and operating in a lithium battery at 4.7 V is prepared by co-precipitation of metal oxalates followed by annealing. Our investigation demonstrates that the designed electrode formulation including Ni, Cu, Mn and Fe may actually ensure suitable structural and morphological characteristics, as well as an extended stability in cells operating at 25 °C and 55 °C. Indeed, the LiNi0.35 Cu0.1 Mn1.45 Fe0.1 O4 cathode shows reversible capacities of 108 mAh g −1 at 0.75C and 91 mAh g −1 at 1.5C (where 1C is 147 mA g −1 ), with a retention between 84% and 80% after 200 cycles and coulombic efficiency values of about 99%. Notably, optimal cathode composition in terms of metals nature and content avoids material degradation upon cycling and enables stable operation in the lithium cell even at a temperature higher than 25 °C, with satisfactory retention of the initial capacity of 110 mAh g −1, i.e., 77%, after 200 cycles at 0.5C. Therefore, the strategy adopted herein is considered adequate for allowing practical battery application of the high-voltage spinel cathode.